A method to compensate fluorescence induced white point differences in proof-processes by printing liquid fluorescent brightening agents using inkjet - Bohn, Daniel; Dattner, Michael; Fehmer, Stefan; Urban, Peter (Journal of Print and Media Technology Research, 2023)
One of the key goals in producing paper and cardboard in the print industry is to achieve a high whiteness degree. This is usually realized by fluorophores called OBAs (Optical Brightening Agents) or FBAs (Fluorescent Brightening Agents). The heavy use of FBAs in production substrates, while proof substrates contain a varying amount of FBAs, results into serious difficulties in any color management process, especially in terms of a white point correction. In this study, an alternative procedure is presented to achieve an illumination independent colorimetric correlation and a visual match between most proof- and production substrates. This is achieved by printing defined amounts of liquid FBA using inkjet with variable area coverage.